2023
DOI: 10.3390/cryst13030473
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the Complex Components under Temperature Cycling, Random Vibration, and Combined Loading for Airborne Applications

Abstract: The electronic devices suffer great vibration and temperature fluctuation in an airborne environment, which has been always a big challenge for reliability design. In this paper, the reliability of the complex electronic components for airborne applications under a thermal cycling test, random vibration and combined loading has been investigated by experiment tests and finite element simulation. The fatigue life and failure location under different loadings have been compared and discussed, respectively. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Researchers’ studies on delamination mechanisms have mainly focused on thermal stress damage and moisture damage. Explaining the delamination phenomenon from the stress–strain perspective alone, it has been found that, at the delamination interface, mainly due to the interface between the two phases of the material, the plastic deformation of the two-phase material is formed under the action of the alternating shear stress, which ultimately leads to the failure of delamination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At the same time, under the intrusion of moisture, ionic contaminants corrode the chip, and moisture thermal expansion is also the main reason for the device to appear to suffer from the “popcorn” effect [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers’ studies on delamination mechanisms have mainly focused on thermal stress damage and moisture damage. Explaining the delamination phenomenon from the stress–strain perspective alone, it has been found that, at the delamination interface, mainly due to the interface between the two phases of the material, the plastic deformation of the two-phase material is formed under the action of the alternating shear stress, which ultimately leads to the failure of delamination [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. At the same time, under the intrusion of moisture, ionic contaminants corrode the chip, and moisture thermal expansion is also the main reason for the device to appear to suffer from the “popcorn” effect [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…An optimization method is proposed to improve the reliability of plastic packaging devices, which can comprehensively consider various influencing factors. This method uses Moldflow and ANSYS (ANSYS_2020R2) and other software; adopts an orthogonal experimental design method, range analysis method, comprehensive weighted analysis method, and other methods; puts forward better technological parameters and structural parameters in the plastic packaging process; and analyzes the influence degree of various factors [18][19][20][21][22]. This method is a universal method that can effectively select the optimal scheme and solve the same kind of problems.…”
Section: Introductionmentioning
confidence: 99%